Characterisation and purification of Commiphora gileadensis extracts with Antiproliferative activities on breast Cancer cell lines - Abdullah F. Aldairi; Sarah A. Alharbi; Moodi S. Alharbi; Ahmad Alghamdi; Anmar Khan; Mazen Ghaith; Hani Alnadwi; Abdullah Alshehri; Asma Alsubaihi; Ayman Alhazmi (Results in Chemistry)
Breast cancer is a common form of cancer that affects women all over the world. Cancer patients have relied on surgery and radiotherapy, chemically derived medications for treatment, which result in several unpleasant side effects. To overcome these issues, medicinal plants would be used as modern pharmaceutical agents to treat various diseases, such as cancer. The study aims to evaluate the antiproliferative activities of Commiphora gileadensis (L.) C.Chr extracts against breast cancer cell lines MCF-7 and MDA-MB-231. Methods: Commiphora gileadensis (L.) C.Chr was harvested and cleaned; chemical extraction was applied using acetone and methanol, then cell viability was measured. The active extract was characterised via untargeted lipidomics analysis. Results: The acetone extract of Commiphora gileadensis (L.) C.Chr showed growth inhibition against MCF-7 and MDA-MB-231 cell lines with IC50 (57.32 μg/mL) and (49.94 μg/mL), respectively. The methanolic extract showed antiproliferative activities against the MCF-7 cell line with IC50 (306.7 μg/mL) and the IC50 (273.6 μg/mL) for MDA-MB-231. Untargeted lipidomic analysis revealed the presence of various lipid classes in each extract. In the acetone extract, the most abundant lipid compounds are hexosylceramide (39.1 %) and ceramide (18.6 %). On the other hand, the lipidomics analysis of the methanolic extract showed the composition consists primarily of ceramide (69 %). In conclusion, the acetone and methanol extracts of Commiphora gileadensis (L.) C.Chr exhibited cytotoxic properties against breast cancer cell lines.